Search for Cellular Stress Biomarkers in Lymphocytes from Patients with Multiple Sclerosis: A Pilot Study - Grecchi, Sabrina; Mazzini, Giuliano; Lisa, Antonella; Armentero, Marie-Therese; Bergamaschi, Roberto; Romani, Alfredo; Blandini, Fabio; Di Perri, Carol; Scovassi, Anna Ivana (PLOS ONE, 2012)
Multiple Sclerosis (MS) is a chronic disease of the central nervous system, the etiology of which, although not completely known, involves inflammation and autoimmunity. In the present study we aimed at identifying molecular markers of apoptosis, cellular stress and DNA damage in isolated peripheral blood mononuclear cells (PBMCs) of MS patients. The analysis was carried on 19 relapsing-remitting untreated MS patients and 13 healthy individuals. We investigated the emergency-driven synthesis of poly(ADP-ribose) (PAR), the expression level of the constitutive enzyme poly(ADP-ribose) polymerase-1 (PARP-1) and the DNA damage-induced phosphorylation of histone H2AX. PAR accumulation, PARP-1 and phosphorylated H2AX (γH2AX) were detected by immunofluorescence experiments on PBMCs isolated from 19 patients and 13 healthy volunteers. Our results show for the first time a net increased amount in PAR and γH2AX in MS patients compared to healthy individuals. Patients were further subdivided in three groups, according to the neuroimaging (MRI)-based classification of disease phase. Remarkably, we found a positive correlation between the level of γH2AX and MS aggressiveness. In addition, apoptosis in PBMCs was monitored by flow cytometry of both phosphatidylserine exposure (revealed by Annexin V-FITC labeling) and membrane permeability to propidium iodide. Our observations provide the evidence that the number of apoptotic cells was significantly higher in patients compared to healthy individuals, thus suggesting that apoptosis could affect MS lymphocyte function.